A key to ageing goslings of the Hawaiian Goose Branta sandvicensis - Hunter, Janet M (Wildfowl, 1995)
The pattern of feather emergence in the goslings of captive Hawaiian Geese, or Nene, was photographed and scored visually to provide a guide for ageing goslings in the wild. The mean age at fledging was 68 days (range 58-77) and the mean age at which the juveniles took on an adult appearance was 137 days (range 199-150). The ability to determine the age of Nene goslings will enable field researchers to keep track of wild broods, thus allowing reliable assessments of recruitment, mortality and population size.